(untitled) (Research, Society and Development, 2020)
The early nineteenth century was marked by many social, economic and cultural transformations in organizations. An element of strong influence on the survival of companies since that time was management. Within the organizational studies, several scholars sought ways to improve the way they manage. From the changes in the world historical context in which the management dimension was transformed, the present work aims to reflect on the evolution of the way management is characterized in organizational studies. Through a bibliographical and qualitative research, it was possible to gather sources to make an analysis and to understand the transformations of the management in the theory of the organizations. The results showed that management approaches, over the decades, show convergences and divergences among themselves. Analyzing the changes in the form of communication regarding flexibility in decision making, making it possible to conclude that the knowledge and learning of the managers were fundamental in the evolution of management given the dynamism and uncertainties of the organizational environment. By observing how management practices have been reshaped and gained new insights through organizational theories, it is hoped that new approaches and theories will emerge to modify the way of managing contemporary organizations.